AKUNTABILITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN TATANGA KOTA PALU (STUDI PELAYANAN PENGURUSAN KTP) - Al- Kafiah, M. Kafrawi (Katalogis, 2014)
The objectives of this study is analyzing accountability of public service in managementIdentity Card at tatanga District Office and the obstructed factors. The method used in this study is qualitative research, to describe the phenomena based on the fact in the research focus. The population of this study is the stake holders of Tatanga District and the public service users. Sample selection used purposive technique by selecting 6 (six) informants. Technique of data collection in this study consisted of observation, interview and document. The result of the study showed that the accountability of public service in management Identity Card at the offfice of Tatanga District was less maximal. This was proved by 3 (three) indicators considered to be Â a starting point, they are service reference, attention to the public and solution. Only 1 (one) indicator showed the accountability of service is the solution. It was given by the goverment of the Tatanga District for the public service users had been maximally implemented. While indicator of service reference and attention to the public had not got maximal categories yet. The factors that obstructed the accountability of public service in management Identity Card at Tatanga District offfice which is found in this study were unavailability of equipment to create ID card. Thus, the duty of the District government officials in service only confined to ID card. Then the people have to complete it to another district office or Civil Registration in Palu. Besides, the service provided from district government in management Identity Card still oriented on arrangement or simply impressed very normative, less committed to adjust servicing values or norms that exist in society in order to create a quality of service that is oriented on customer satisfaction.